Cover Picture: Electrochemically Induced Release of a Luminescent Probe from a Rhenium‐Containing Metallopolymer (ChemPlusChem 1/2013). Issue 1 (22nd January 2013) - Valenti, Giovanni; O'Reilly, Emmet J; McNally, Andrea; Keyes, Tia E.; Marcaccio, Massimo; Paolucci, Francesco; Forster, Robert J.
<x xml:space="preserve">Abstract</x> The cover picture shows the release of the luminescent rhenium coordination complex (yellow spheres) in solution. This release is triggered by electrochemical stimulus applied through the cable to the metallopolymer, which is represented by the splash of blue paint. The irreversibility of the electrochemical release is highlighted by holes in the graph paper. G. Valenti, F. Paolucci, R. J. Forster, and co‐workers outline the photophysical and electrochemical properties of a novel metallopolymer containing [Re(bpy)(CO)3]+ moieties coordinated to a poly(4‐vinylpyridine) polymer chain in their Full Paper on page 55 ff. Release of the metal complexes can be triggered by oxidation or reduction of the rhenium complex.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>